2017
DOI: 10.5005/jp-journals-10028-1223
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Retinal Nerve Fiber Layer Changes by Cirrus High-definition Optical Coherence Tomography in Myopia

Abstract: Introduction To evaluate the relationship between retinal nerve fiber layer (RNFL) thickness measured by Cirrus high-definition (HD) optical coherence tomography (OCT) and the axial length and refractive error of the eye.Materials and methods A total of 100 eyes of 100 healthy subjects (age 20-34 years with M/F ratio of 57/43), comprising 50 eyes with emmetropia [spherical equivalent (SE) 0 D], 25 eyes with moderate myopia (SE between -4 D and -8 D), and 25 eyes with high myopia (SE between -8 D and -12 D) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…[ 12 ] However, for most myopic patients without POAG, numerous studies have reported that the RNFL was also abnormally thin due to axial extension and atrophy of the retina. [ 2 5 6 ] In our study, a thinner RNFL was found in all myopic groups, especially for the moderate- and high-myopic groups. In the high-myopic group, the thinning included almost all the observational parameters.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…[ 12 ] However, for most myopic patients without POAG, numerous studies have reported that the RNFL was also abnormally thin due to axial extension and atrophy of the retina. [ 2 5 6 ] In our study, a thinner RNFL was found in all myopic groups, especially for the moderate- and high-myopic groups. In the high-myopic group, the thinning included almost all the observational parameters.…”
Section: Discussionsupporting
confidence: 56%
“…If the accuracy of the measured results is poor, the percentages of misdiagnoses will increase. [ 5 6 ] In the present study, we used SD-OCT, which is widely used in the early diagnosis of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the RNFL thickness is negatively correlated with the AXL. Singh et al and Kang et al found that the mean RNFL thickness decreased by 3.74 μm and 2.2 μm, respectively, for each mm increase in the AXL [ 69 , 70 ] Additionally, this thinning of the RNFL in highly myopic eyes is not uniformly distributed, being greater in the lower quadrant (134.8 ± 17 μm vs. 109.9 ± 15 μm, p > 0.001) in emmetropes vs. high myopes, respectively. It has also been observed that myopic eyes have a significantly greater rate of decline in RNFL during follow-up than controls.…”
Section: Rnfl Thickness Measurement By Octmentioning
confidence: 99%
“…The mean RNFL thickness: 110.9 ± 10 μm vs. 89.8 ± 9 μm in highly myopic patients compared to emmetropic patients ( p < 0.001) [ 69 ].…”
Section: Figurementioning
confidence: 99%
“…It has been found that actual scanning radius in eyes with greater axial length (myopic eyes) could be longer than 1.73 mm due to magnification effect, so using same-sized scan circle for measuring pRNFL in patients with different degrees of myopia might be misleading because the RNFL thickness decreases with increasing distances from the optic disk [26]. Therefore, the pRNFL results of the patients with myopia need to be adjusted according to the axial length (AL).…”
Section: Data Processing Of Prnfl and Pvdmentioning
confidence: 99%